Supporting immigrant language learning on smartphones: A field trial. Issue 2 (3rd July 2017) - Jones, Ann; Kukulska-Hulme, Agnes; Norris, Lucy; Gaved, Mark; Scanlon, Eileen; Jones, Jan; Brasher, Andrew
Abstract: The challenge of supporting immigrant language-learning and social integration has increased recently, leading to initiatives and projects that aim to provide assistance, including using smartphones in the course of daily activities. However, most of the Mobile Assisted Language Learning (MALL) literature focuses on classroom based learning thereby leaving a gap in understanding the learning in informal settings. This paper discusses a UK field trial of the European funded MASELTOV project, which developed a suite of smartphone tools and services (the 'MApp') to help immigrants' language learning and social inclusion in four European cities. MApp tools and services include language lessons designed to assist informal learning in everyday life, focusing on situational language needs and a social forum for peer support, cultural information, comments and practice. The paper reports on interview data and social forum use. Our findings suggest that the MApp helps immigrants with their confidence; with relevant, practical language learning and practice of different language skills, and also supports social learning. Studying and practising language skills in the locations, and at times, of learner's choice, along with access to a social forum for socio-emotional support and feedback, it is a powerful combination of informal mobile language learning.